РАЗРАБОТКА РЕЖИМОВ ОХЛАЖДЕНИЯ ЖЕЛЕЗНОДОРОЖНОГО КОЛЕСА НА ВЕРТИКАЛЬНОЙ ЗАКАЛОЧНОЙ МАШИНЕ С ПОМОЩЬЮ МАТЕМАТИЧЕСКОЙ МОДЕЛИ РАСЧЕТА СКОРОСТЕЙ ОХЛАЖДЕНИЯ (Modern Problems of Metallurgy, 2020)
To increase the resistance to the formation of thermal origin operational defects on rail wheel rolling surface has been developed a new chemical composition of the steel. For the development of heat treatment it was necessary to create a mathematical model for calculating the cooling rates over the section rim with accelerated cooling. The models of the temperature distribution and cooling rates on the cross section of the rim after cooling with the help of vertical quenching machine, obtained through the solution of the differential equation of heat conduction (Fourier equation), enabled the development of heat treatment regimes that ensure reception of a given set of mechanical properties of railway wheels of the experimental steel.